Bibliometric Analysis of Microplastic Pollution Monitoring in Water Bodies - Loso Judijanto (Westscience Press, 2026)
This study presents a bibliometric analysis of research on microplastic pollution monitoring in water bodies to identify intellectual structure, collaboration patterns, and thematic evolution within the field. Data were retrieved from a scientific database and analyzed using bibliometric mapping techniques with VOSviewer, focusing on co-authorship, co-occurrence of keywords, co-citation, and country-level collaboration networks. The results reveal that research activity is highly concentrated around core themes such as microplastic occurrence, polymer identification, aquatic ecosystem contamination, and ecotoxicological impacts. Keyword analysis shows a strong emphasis on environmental monitoring, pollution pathways in freshwater and marine systems, and biological exposure through ingestion and toxicity. The co-authorship and institutional networks indicate the presence of several well-established but partially fragmented research groups, with limited cross-cluster integration. At the country level, China, the United States, and India emerge as dominant contributors and central hubs in global collaboration networks, while European and other regions form distinct secondary clusters. The study highlights a transition in the research landscape from descriptive monitoring toward more advanced analytical approaches, including risk assessment and standardized detection methodologies.